Bharatiya Bhasha in Higher Education Under NEP 2020: Implications for Literary Writing and Literary Studies - Ajit M. Karigar (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
The National Education Policy 2020 represents a decisive shift in India’s educational philosophy by foregrounding the role of Bharatiya Bhasha in higher education. Language, however, is not merely a medium of instruction; it is also the foundation of literary creativity, interpretation, and critical discourse. This paper examines the vision of NEP 2020 with specific reference to Bharatiya Bhasha in higher education and analyses its implications for literary writing and literary studies. It explores how the use of Indian languages in teaching and research can deepen literary comprehension, encourage creative expression, and strengthen engagement with regional and indigenous literary traditions. At the same time, the paper critically reflects on challenges such as the lack of academic resources, faculty preparedness, and institutional readiness for literary scholarship in Bharatiya Bhasha. The study highlights emerging possibilities, including translation initiatives, multilingual pedagogy, curriculum reform and digital platforms that support literary production and criticism. The paper argues that a gradual, inclusive, and balanced implementation of NEP 2020 can rejuvenate literary studies by fostering culturally rooted yet globally connected scholarship.